Reintroduction modifies the intraspecific variations of symbiotic microbes in captive bred Chinese giant salamander - Feng, Jianyi; Zhu, Wei; Jiang, Jianping; Zhao, Chunlin; Sun, Zijian; Jiang, Wansheng; Luo, Qinghua; Zhao, Tian (Frontiers in Microbiology, 2022)
Microorganisms play as fundamental contributors to maintain hosts’ fitness, which can be shaped by external environment. Moreover, symbiotic microbiome also varied within species (e.g., between sexes and developmental stages). However, we still need more studies to quantify whether the intraspecific variation patterns of symbiotic microbes can be modified with the change of environment. The Chinese giant salamander (CGS; Andrias davidianus) is a Critically Endangered species. Despite quantitative captive bred individuals were released to rebuild wild populations, the effectiveness is limited. More importantly, no studies have revealed the adaptation of released CGSs to the complex field conditions. In the present study, we explored whether reintroduction can reshape the intraspecific variations of symbiotic microbiota in captive bred CGSs. We found no significant difference of symbiotic microbiome in captive bred males and females, but released males and females differed significantly in skin microbiome. Juveniles had higher diversity of microbial symbiont than adults in hatchery, but lower diversity in field. Moreover, dominant bacterial taxa differed between juveniles and adults in both hatchery and field. Importantly, this symbiotic microbiome variations within species can be modified (alpha and beta diversity, and community composition) when captive bred individuals were released to the field, associating with the change of living environment, as well as the specific behavior within species (e.g., movement patterns and foraging activities). Overall, we observed a lower alpha diversity and higher relative abundance of Chryseobacterium, Plesiomonas, and Acinetobacter in the bacterial community of captive bred individuals. Instead, higher alpha diversity of symbiotic microbiota and higher relative abundance of S24-7 and Lactobacillus was detected in released individuals. These modifications may associate with the change of living environment, as well as the specific behavior within CGSs (e.g., movement patterns and foraging activities). Future studies can incorporate other approaches (e.g., blood physiology) to evaluate the growth and health of reintroduced CGSs.